2020
DOI: 10.1017/s0016756820000473
|View full text |Cite
|
Sign up to set email alerts
|

Genesis of the Bagenheigeqier Pb–Zn skarn deposit in Inner Mongolia, NE China: constraints from fluid inclusions, isotope systematics and geochronology

Abstract: Most skarns are found near the pluton or in lithologies containing at least some limestone. However, recent research has shown that neither a pluton nor limestone is necessarily required to form a skarn deposit. The newly discovered Bagenheigeqier Pb–Zn skarn deposit is located in NE China. The skarn and Pb–Zn orebodies occur in volcanic lithologies of the Baiyin’gaolao Formation and are controlled by NE–SW-trending faults. The nearest pluton is a granite porphyry, at a distance of 20–250 m from the orebodies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 139 publications
(181 reference statements)
1
2
0
Order By: Relevance
“…Combined with previous bulksulfur isotope analyses (Figure 10A), high δ 34 S values (up to 5‰) do not exclude a small contribution from wall rocks (sedimentary or metamorphic rocks). Such a sulfur isotopic composition, consistent with the sulfur isotope composition of the other gold deposits in the Luxi district (Figure 10A), is common in skarn-type deposits (e.g., Shu et al, 2013;Peng et al, 2016;Cai et al, 2021).…”
Section: Source Of Ore-forming Materialssupporting
confidence: 77%
“…Combined with previous bulksulfur isotope analyses (Figure 10A), high δ 34 S values (up to 5‰) do not exclude a small contribution from wall rocks (sedimentary or metamorphic rocks). Such a sulfur isotopic composition, consistent with the sulfur isotope composition of the other gold deposits in the Luxi district (Figure 10A), is common in skarn-type deposits (e.g., Shu et al, 2013;Peng et al, 2016;Cai et al, 2021).…”
Section: Source Of Ore-forming Materialssupporting
confidence: 77%
“…Studies showed that the distribution of lead-zinc deposits was basically consistent with that of skarn (Cai et al, 2021). The types and characteristics of pollutants in the surrounding environment created by lead-zinc mines were quite different depending on the topography, climate, as well as soil physical and chemical properties of the contaminated area (Feng et al, 2020).…”
Section: Analysis Of Mineral Species Differences Of Heavy Metal Pollu...mentioning
confidence: 92%
“…Skarn Au-Cu deposits, despite being less frequent than porphyry Cu-Au deposits, often exhibit elevated grades of gold and copper [6], thus garnering considerable attention from economic geologists [4,[6][7][8]. Previous research endeavors aimed at comprehending the genesis of Au-Cu skarn deposits and mainly focused on skarn minerals (e.g., garnet), sulfide geochemistry (pyrite and chalcopyrite), and isotopes (S and Pb), contributing to our understanding of the mineralization process (e.g., [7][8][9][10]). However, the understanding of the mechanisms that trigger gold and copper precipitation in skarn deposits, including water-rock reactions and fluid mixing, remains inadequate.…”
Section: Introductionmentioning
confidence: 99%